2010
DOI: 10.1210/jc.2009-1915
|View full text |Cite
|
Sign up to set email alerts
|

The Subcutaneous Abdominal Fat and Not the Intraabdominal Fat Compartment Is Associated with Anovulation in Women with Obesity and Infertility

Abstract: Abdominal fat is increased in anovulatory women due to a significant increase in SAF and not in intraabdominal fat. SAF and especially abdominal and trunk fat accumulation are associated with anovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…[18][19][20][21] The program was developed according to the recommendations of the National Institutes of Health 22 and was piloted in a singlecenter study. 23,24 It included six outpatient visits and four telephone consultations during a 24-week period.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…[18][19][20][21] The program was developed according to the recommendations of the National Institutes of Health 22 and was piloted in a singlecenter study. 23,24 It included six outpatient visits and four telephone consultations during a 24-week period.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…In addition, high level of AKR1C 1, 2 may further reduce local concentrations of DHT and progesterone. Intra-adipose sex steroid metabolism may play an important role in determining gynoid vs. android patterns of body fat; increased metabolism of progesterone (anti-glucocorticoid action) and synthesis of androgen by AKR1C isoforms were positively correlated with adiposity in women [18,24]. Furthermore, the total amount of steroid within adipose tissue was found 40-400 times greater than plasma [25]; a positive gradient between tissue and plasma was also reported [26].…”
Section: Discussionmentioning
confidence: 95%
“…This set of data indicated that adipose tissues may convert estrogen, progesterone and androgens from their precursors (especially from androstenedione) instead of from cholesterol and subcutaneous fat may be an important steroid-inactivating organ. SAT especially abdominal and trunk fat accumulation, is associated with anovulation, a major feature of PCOS [24]. We compared the mRNA levels of sex steroid synthesis and inactivating enzymes in SAT between PCOS and control women.…”
Section: Discussionmentioning
confidence: 99%
“…Obese women with a BMI >27 kg/m 2 have a relative risk (RR) of anovulatory infertility of 3.1 (95% CI, 2.2-4.4) compared with their lean counterparts with a BMI 20.0-24.9 kg/m 2 (33,34). Body fat distribution also is important because anovulatory women have a greater waist circumference and more abdominal fat than ovulatory women of similar BMI (35). A case-control study of 2,527 women with anovulatory infertility versus 46,718 control subjects (mostly married parous nurses without infertility) noted a relationship between BMI at 18 years of age and the RR of subsequent anovulatory infertility (1.0, BMI 20.0-21.9; 1.3, BMI 24-25.9; 1.7, BMI 26-27.9; 2.4, BMI 28-29.9; 2.7, BMI 30-31.9; and 2.7, BMI >32 kg/m 2 ) (33).…”
Section: Ovulatory Dysfunctionmentioning
confidence: 99%